2023
DOI: 10.1002/adhm.202301485
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride‐Based siRNA Vectors with Self‐Produced O2 Effects for Targeting Combination Therapy of Liver Fibrosis via HIF‐1α‐Mediated TGF‐β1/Smad Pathway

Abstract: Hypoxia is an important feature, which can upregulate the hypoxia‐inducible factor‐1α (HIF‐1α) expression and promote the activation of hepatic stellate cells (HSCs), leading to liver fibrosis. Currently, effective treatment for liver fibrosis is extremely lacking. Herein, a safe and effective method is established to downregulate the expression of HIF‐1α in HSCs via targeted delivery of VA‐PEG‐modified CNs‐based nanosheets‐encapsulated (VA‐PEG‐CN@GQDs) HIF‐1α small interfering RNA (HIF‐1α‐siRNA). Due to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Hepatic hypoxia has been proved to upregulate the hypoxia-inducible factor HIF-1α, thereby activating HSCs leading to promote the initiation and progression of liver fibrosis . With sufficient oxygen, the EGLN protein will be activated and hydroxyllated the ODD domain of HIF-1α, thereby binding and polyubiquitinating HIF-1α and leading to its degradation to enhance cellular ferroptosis. , Therefore, the ability of VPSGCNs@TSI to generate oxygen via photosplitting water is essential for liver fibrosis therapy. The mechanism of VPSGCNs@TSI-mediated water splitting is shown in Figure A.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic hypoxia has been proved to upregulate the hypoxia-inducible factor HIF-1α, thereby activating HSCs leading to promote the initiation and progression of liver fibrosis . With sufficient oxygen, the EGLN protein will be activated and hydroxyllated the ODD domain of HIF-1α, thereby binding and polyubiquitinating HIF-1α and leading to its degradation to enhance cellular ferroptosis. , Therefore, the ability of VPSGCNs@TSI to generate oxygen via photosplitting water is essential for liver fibrosis therapy. The mechanism of VPSGCNs@TSI-mediated water splitting is shown in Figure A.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Cells cannot survive without oxygen, and hypoxia will lead to liver fibrosis via mediating chronic inflammation and ECM deposition. , With the further development of liver fibrosis, hepatic sinus capillarization aggravates and worsens the degree of liver hypoxia, forming a vicious circle. Tissue hypoxia will also upregulate hypoxia-inducible factor-1α (HIF-1α) expression and promote HSC activation, leading to liver fibrosis. , As an important transcription factor in regulating liver fibrosis, HIF-1α and its downstream factors are expected to be an effective way to alleviate liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] Hypoxia can induce the upregulation of HIF-1α, activating hepatic stellate cells, which ultimately results in hepatic fibrosis. [ 42 ] Yexiaodan [ 43 ] discovered that inhibiting the HIF-1α/PPARγ signaling pathway can decrease inflammation and steatosis. The ESR1 expression is lower in men than women, but ESR1 knockout will cause insulin resistance phenotype, presenting obesity, glucose intolerance, liver steatosis, and metabolic inflammation of adipose tissue and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, a large body of evidence has shown that HIF-1a is closely associated with hepatic fibrosis (214). HIF-1a is stably expressed during hypoxia and forms a dimer with HIF-1b, inducing downstream gene transcription and hypoxia response (215)(216)(217). HIF-1a regulates VEGF under hypoxic conditions, controls angiogenesis, cell proliferation, and metastasis, and plays an important role in the occurrence and development of hepatic fibrosis and HCC (77,78,218,219).…”
Section: Yap/hif-1a Signalingmentioning
confidence: 99%
“…Hypoxia is an important feature of hepatic fibrosis, which can upregulate the expression of HIF-1a, promote the activation of HSCs, and lead to hepatic fibrosis. Improving the anoxic environment at the site of hepatic fibrosis and downregulating the expression of HIF-1a to the maximum extent can improve the therapeutic effect of hepatic fibrosis (215,216). HIF-1a is known to stimulate collagen synthesis and chemotaxis in HSCs, as well as induce HSC migration, with activated HSCs known to play a Shan et al 10.3389/fonc.2023.1196298 Frontiers in Oncology frontiersin.org 14 dominant role in sinusoidal structural changes during fibrosis through crosstalk with LSECs.…”
Section: Yap/hif-1a Signaling and Hepatic Fibrosismentioning
confidence: 99%